C-Peptide Promotes Cell Migration by Controlling Matrix Metallopeptidase-9 Activity Through Direct Regulation of β-Catenin in Human Endometrial Stromal Cells - Abdul Khaliq, Sana; Umair, Zobia; Baek, Mi-Ock; Chon, Seung Joo; Yoon, Mee-Sup (Frontiers in Cell and Developmental Biology, 2022)
The motility of endometrial stromal cells (ESCs) contributes to the restoration of the endometrial functional layer and subsequently supports the trophoblast invasion during early pregnancy. Following ESCs differentiation through decidualization in response to progesterone during the menstrual cycle and embryo implantation, decidualized ESCs (D-ESCs) have greater motility and invasive activity. The human proinsulin-connecting peptide (C-peptide) is produced in equimolar amounts during the proteolysis of insulin in pancreatic β-cells. However, the function of C-peptide in the cellular motility of the human endometrium remains unexamined. In the present study, C-peptide was identified as a determinant of undecidualized human endometrial stromal cells (UnD-ESCs) migration. C-peptide promoted the migration and invasion of UnD-ESCs and trophoblast-derived Jeg3 cells, but not that of ESCs post decidualization, a functional and biochemical differentiation of UnD-ESCs. Both Akt and protein phosphatase 1 regulated β-catenin phosphorylation in UnD-ESCs, not D-ESCs, thereby promoting β-catenin nuclear translocation in C-peptide-treated UnD-ESCs. C-peptide was also observed to increase matrix metallopeptidase-9 (MMP9) activity by increasing MMP9 expression and decreasing the expression of metallopeptidase inhibitor 1 (TIMP1) and TIMP3. Their expression was modulated by the direct binding of β-catenin in the regulatory region of the promoter of MMP9, TIMP1, and TIMP3. Inhibition of either β-catenin or MMP9 dampened C-peptide-enhanced migration in UnD-ESCs. Together, these findings suggest that C-peptide levels are critical for the regulation of UnD-ESC migration, providing evidence for the association between C-peptide levels and the failure rate of trophoblast invasion by inducing abnormal migration in UnD-ESCs in hyperinsulinemia or PCOS patients.